Risk factors for erosive tooth wear in a healthy lifestyle - Kynsveen, Birgit; Sæterstad, Maren Lunde (UiT Norges arktiske universitet, 2016)
Dental erosive wear is of growing concern among clinicians, and it is of general belief that the prevalence of erosive wear among children, adolescents and young adults has increased. The aim of this study was to investigate risk factors for erosive tooth wear in a group of physically active people in a training centre in Tromsø, Norway. The hypothesis was that individuals with a pronounced healthy lifestyle with frequent physical exercise and specific dietary habits could have an increased risk for developing erosive tooth wear. 211 people who visited the training centre completed a questionnaire anonymously, with age ranging from 15 to 67 years old. The results showed that the participants had good oral hygiene habits and regular visits to the dentist. Most of them did not show increased risk in the pattern of consumption of sour drinks, sour foods, and sports drinks. Some of them drank nutritional supplements during exercise, most of the participants with high intake of these supplements were men. Most of the participants in this study did not report habits that indicated an increased risk for erosive tooth wear in their healthy lifestyle.